2016
DOI: 10.1200/jco.2015.66.3476
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Intensity Transplantation for Lymphomas Using Haploidentical Related Donors Versus HLA-Matched Sibling Donors: A Center for International Blood and Marrow Transplant Research Analysis

Abstract: Related donor haploidentical hematopoietic cell transplantation (Haplo-HCT) using posttransplantation cyclophosphamide (PT-Cy) is increasingly used in patients lacking HLA-matched sibling donors (MSD). We compared outcomes after Haplo-HCT using PT-Cy with MSD-HCT in patients with lymphoma, using the Center for International Blood and Marrow Transplant Research registry. Materials and MethodsWe evaluated 987 adult patients undergoing either Haplo-HCT (n = 180) or MSD-HCT (n = 807) following reduced-intensity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
129
4
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 219 publications
(153 citation statements)
references
References 32 publications
13
129
4
7
Order By: Relevance
“…[22][23][24][25] Furthermore, HSCT after PD-1 blockade may be associated with lower than expected relapse rates. CIR at 1 year in this study compares favorably to that expected for this cohort based on the Disease Risk Index mix of patients (14% vs 26%).…”
Section: Absolute Cd4+ T Cellsmentioning
confidence: 99%
“…[22][23][24][25] Furthermore, HSCT after PD-1 blockade may be associated with lower than expected relapse rates. CIR at 1 year in this study compares favorably to that expected for this cohort based on the Disease Risk Index mix of patients (14% vs 26%).…”
Section: Absolute Cd4+ T Cellsmentioning
confidence: 99%
“…66,[80][81][82][83][84] In 475 patients with a variety of hematologic malignancies, Bashey et al showed matched sibling, optimally (10 of 10 HLA allele) matched unrelated donor, and haploidentical transplants all had similar 2-year disease-free survival (ie, 56% vs 50% vs 54%). 80 In 459 patients, Raiola et al showed 4-year disease-free survival was 43% after haploidentical transplantation, 32% after matched sibling transplantation, 36% after matched unrelated donor transplantation, 34% after mismatched unrelated donor transplantation, and 33% after unrelated cord blood transplantation.…”
Section: Haploidentical Vs Matched Hematopoietic Transplantationmentioning
confidence: 99%
“…66 Two studies in lymphoma patients showed similar outcomes after haploidentical transplants with high-dose cyclophosphamide and matched sibling or unrelated donor transplants. 83,84 In a nonrandomized, prospective, multicenter trial in 450 adult AML patients in CR1 at transplant, the Beijing group found 3-year disease-free survival was 74% after haploidentical transplantation and 78% after matched sibling transplantation. 79 A retrospective pair-matched study in adult AML patients in CR1 showed similar results after haploidentical transplants performed in China and matched unrelated donor transplants performed in Europe.…”
Section: Haploidentical Vs Matched Hematopoietic Transplantationmentioning
confidence: 99%
“…Indeed, a recent study of lymphoma patients receiving either haplo SCT with PTCy or HLAmatched sibling SCT came to the same conclusion. 12 It may be argued that the comparison is unfair because the haplo transplants used PTCy, whereas the MUD transplants did not. Support for this argument comes from recent reports showing good survival and low incidence of chronic GVHD after MUD SCT with PTCy.…”
mentioning
confidence: 99%